2011
DOI: 10.1111/j.1468-4446.2010.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegaphobia: derogatory discourses of veganism and the reproduction of speciesism in UK national newspapers1

Abstract: This paper critically examines discourses of veganism in UK national newspapers in 2007. In setting parameters for what can and cannot easily be discussed, dominant discourses also help frame understanding. Discourses relating to veganism are therefore presented as contravening commonsense, because they fall outside readily understood meat-eating discourses. Newspapers tend to discredit veganism through ridicule, or as being difficult or impossible to maintain in practice. Vegans are variously stereotyped as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
168
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(178 citation statements)
references
References 23 publications
6
168
0
4
Order By: Relevance
“…Media representations of vegans as ascetic (Cole and Morgan, 2011) are countered by the exhortation: "Start with food you already love.…”
Section: Whilst the Political Effects Of Different Ethical Consumptiomentioning
confidence: 99%
See 4 more Smart Citations
“…Media representations of vegans as ascetic (Cole and Morgan, 2011) are countered by the exhortation: "Start with food you already love.…”
Section: Whilst the Political Effects Of Different Ethical Consumptiomentioning
confidence: 99%
“…Cole and Morgan (2011) found that women are the target of both anti-vegan and sexist discourses through feminisation tactics which present vegans (and women) as over sensitive and irrational (Cole and Morgan, 2011). The gendering of veganism as feminine and emotional is similar to that of vegetarianism, where (eating) meat is equated with heterosexual masculinity (Nath, 2012): a powerful discourse that feminist vegetarian/vegans have critiqued (Adams, 1990;Duvnjak, 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations